Patterns of use of time by family caregivers of elderly persons with dementia - Elcyana Bezerra Carvalho; Anita Liberalesso Neri (Revista Brasileira de Geriatria e Gerontologia)
Abstract Objectives: to describe patterns of use of time in family caregivers of elderly people with dementia, considering the characteristics of the caregivers, the care recipients and the context. Method: Fifty family caregivers of elderly people with intermediate and high levels of physical and cognitive disability participated in an interview about time spent on obligatory care activities over four periods of six hours during a 24-hour period. In addition, a questionnaire about social activities, scales of physical and cognitive functionality of the elderly and an inventory of burden in the family caregivers were applied. Results: 88.0% of the caregivers were women, with a mean age of 57.9 (±11.2) years; 45.92% of the time of the caregivers was used in care activities, 36.92% in discretionary activities, 31.17% in recuperation, and 25.67% in the obligatory activities of the life of the caregiver. The greater the dependence, the longer the care, the less time for self-care and greater the caregivers’ subjective burden. Conclusion: The level of dependence of elderly persons affected by dementia results in an increase in caregiving time and competes with other activities performed by the caregiver. Reorganization of the use of time by family caregivers and provision of formal support can reduce the caregiving burden and benefit the well-being of caregivers.